„Glücklich ein Mann, der JHWH fürchtet!“ (Ps 112,1) JHWH-Furcht als ethisches Prinzip in Ps 111/112 - Kathrin Gies (Protokolle zur Bibel, 2016)
This paper investigates the significance of the concept of the Fear of God within ethical questions in Ps 111/112. In the past, the approach regarding Old Testament ethics has been rather descriptive and situated within the field of history of religions (e.g. E. Otto). However, if ethics are understood as part of an ongoing discourse into which the reader enters, new perspectives will be gained. Readers and texts become thus partners in a discussion about how humans ought to act. Similarly, older research inquired as to the historical development of the multifaceted notion of the Fear of God from numinous to normative (e.g. J. Becker following R. Otto). Again, one can also consider the openness of the concept as condition for its relevance, as it combines anthropological, theological, ethical and eschatological aspects. Within the book of Psalms the twin psalms 111/112 show these different aspects of the Fear of God: YHWH shows himself as Holy and awesome with his just deeds in history. It is man’s task to act according to this divine justice and order. Therefore, the Fear of God can be considered as a universal ethical principle, albeit one that can only be fulfilled when the wicked have come to an end. Psalms 111/112 will be analyzed in regard to how the concept of the Fear of God is part of the discourse on standards of conduct. It will be argued that the two psalms help the one who prays to reassure himself of the values at stake, especially where no legal sanction is enforceable.